Photopneumatic therapy for the treatment of acne - Rungsima Wanitphakdeedecha (2018)
Background: A wide variety of laser and light-based therapies have been utilized for acne vulgaris; however, current techniques have been limited by photosensitivity issues or inconsistent results. Objective: To determine the clinical efficacy and side-effect profile of photopneumatic therapy for the treatment of facial acne vulgaris. Methods: Twenty adults with mild to severe facial acne vulgaris received 4 successive treatments at 2-week intervals with a combined photopneumatic device (intense pulsed light [IPL]: fluences=3.6-4.2 J/cm2; negative pressure=3 psi). Clinical improvement was evaluated on a quartile grading scale using comparative digital photographs at baseline, and 1 month and 3 months after the final treatment. Acne lesion counts were obtained at baseline, prior to each treatment session, and at the end of the study. Results: Modest reduction in acne lesion counts and global clinical improvement was seen in the majority of patients. Patients with severe acne experienced the most clinical improvement. Side effects were mild and limited to transient erythema and rare purpura. Most patients experienced acne worsening early in the treatment course. Conclusion: Photopneumatic therapy is a safe and effective treatment for acne vulgaris. Patients with more severe acne respond best to treatment. Copyright © 2009 Journal of Drugs in Dermatology.